Associations between Prepartum and Postpartum Maternal Symptoms of Depression, Anxiety and Stress Related to COVID-19 Pandemic and Childhood Sensory Avoidance: Results from Conception Study - Delphine Aubin; Jessica Gorgui; Anick Bérard; Sarah Lippé (Children, 2024)
Background: Prepartum and postpartum maternal symptoms of stress, anxiety and depression are likely to influence the child’s sensory processing through hormonal alterations and an influence on mother–child interactions. Objective: We investigated the associations between maternal prepartum and postpartum symptoms of depression, anxiety and stress related to the COVID-19 pandemic and childhood sensory avoidance at 18 months. Methods: Longitudinal data from 409 participants followed during the COVID-19 pandemic were used. They completed questionnaires during pregnancy and up to 18 months after delivery. Maternal distress symptoms were assessed prenatally and at 18 months postnatally using the Edinburgh Postnatal Depression Scale, the Generalized Anxiety Disorders 7-item Scale and a 10-point scale assessing the level of stress felt related to the COVID-19 pandemic. Child sensory avoidance was assessed at 18 months postpartum using the Infant/Toddler Sensory Profile—Second Edition. Pearson correlations and multiple regressions measured the associations between maternal distress symptoms and child sensory avoidance. Results: Prepartum and 18-month postpartum maternal depression and anxiety were significantly correlated with childhood sensory avoidance (p < 0.05). Together, these variables explained 7.18% (F = 2.12, p < 0.05) of the variance of childhood sensory avoidance. Conclusions: These results support the contributory effect of prepartum and postpartum maternal distress on childhood sensory development.